The Urgency of Gresik Wooven Sarong as Local Wisdom Research - Harjanti, Wulandari; ., Ujianto; Riduwan, Akhmad (International Journal of Scientific Research and Management (IJSRM), 2020)
Local wisdom is seen as something that contains goodness for the lives of the people who embrace it. With the development of local industries, local excellence will become the potential for specific resources that are part of the scope of regional development planning. In one regional community in Gresik district, the community weaves traditionalist sarong and strongly holds local traditions which it considers as a legacy from their ancestors. From a tradition within a group / community comes the character in the group, this trait gives rise to local wisdom, namely; religious Islam, Mutual Cooperation and Panggungan (souvenirs) are inherent in the hospitality of the community in Gresik Regency which is pursued as a terminology in driving Small businesses in Gresik that continue to develop with the help of the Gresik district government